Two Nipped-B-Like Protein A (Nipbla) Gametologs in Chinese Tongue Sole (Cynoglossus semilaevis): The Identification of Alternative Splicing, Expression Pattern, and Promoter Activity Analysis - Zhu, Ying; Shi, Rui; Yang, Qian; Zhang, Mengqian; Chen, Songlin; Wang, Na (Frontiers in Marine Science, 2022)
In mammals, the mutation of nipbl leads to Cornelia de Lange Syndrome (CdLS), characterized by low birth weight, short stature and structural abnormalities of the skeleton, heart, and gut. In Chinese tongue sole (Cynoglossus semilaevis), a typical marine fish exhibiting sexual size dimorphism, the nipbl homologue gene (nipbla) was also screened with female-higher expression level by somatotropic and reproductive tissues’ transcriptomic analysis. In present study, two nipbla genes named as nipbla-w and nipbla-z were identified from W and Z chromosome of C. semilaevis, respectively. Similar with other mammalian and fish species nipbl, the two homologue proteins of C. semilaevis contained two conserved domain-cohesion_HEAT and Nipped-B_C. The phylogenetic tree analysis showed that these two nipbla gametologs proteins were firstly clustered together, and then grouped with other fish species. At least two types of alternative splicing sites were observed in 12 exon of the nipbla-z gene, which produced nipbla-z-tv1 and nipbla-z-tv2. And the sex-biased expression patterns of different nipbla-w and nipbla-z transcripts in female and male tissues were revealed by qPCR. The highest expression level of nipbla-w was observed in female gonad. While, nipbla-z-tv1 exhibited relatively high expression in muscle, liver, gonad, and brain, but nipbla-z-tv2 only showed its expression superiority in muscle of male. The promoter regions of nipbla genes were amplified and their transcription activity were successfully verified by dual-luciferase reporter system. After nipbla-w and nipbla-z knockdown in the brain cell lines by RNA interference, a series of growth-related genes were influenced, including bmp4, wnt11, and spred2. The prediction of transcription factors suggested that c-jun, SRY, POU1F1a, MyoD, STAT5A, and Nfic might be putative up-stream regulatory factors for nipbla, among them, c-jun has been verified to effectively regulate transcriptional activity of nipbla. The identification of two nipbla genes provided important data for interpreting the sexual size dimorphism in C. semilaevis.